A method for preparing a starch-based biodegradable meal box
Patent Information
- Application Number
- CN202611238604.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-15
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]现有共混与表面改性技术存在材料界面适配性的固有核心缺陷,淀粉极性基体与疏水改性组分存在显著热力学不相容特性,致使两相界面结合松散、界面相容性极差,不仅无法实现疏水组分的均匀稳定分散,还会在潮湿环境下引发界面剥离、孔隙吸水等问题,造成材料防水性能、力学性能快速衰减且稳定性极差,无法兼顾淀粉基材料生物降解特性与长效耐水使用性能,成为制约高性能淀粉基可降解制品产业化应用的关键技术瓶颈
[0024]1.本发明所述的一种淀粉基生物降解餐盒的制备方法,本发明通过构建三元热稳定协同体系,从根本上改变了淀粉基材料在热塑加工过程中的热降解行为,传统方法中淀粉在130~140℃加工温度下即出现明显的变色和分子链断裂现象,而本发明方法能够在145~155℃的加工温度下保持淀粉分子链的完整性,热降解率降低了60%以上,这使得在保持产品生物降解性能的前提下,淀粉的填充量可以提高至45%~50%,与传统方法相比提高了10~15个百分点,有效降低了生物降解塑料的使用量,从而降低了原材料成本并提升了产品的环保性能。
Smart Images

Figure CN122878634A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable materials, specifically a method for preparing a starch-based biodegradable lunch box. Background Technology
[0002] Starch-based polymer materials have outstanding advantages such as complete biodegradability, green environmental protection, and easy availability of raw materials. They are the core green materials to replace traditional plastics in the field of disposable tableware and packaging products. However, their molecular chains are rich in a large number of hydrophilic hydroxyl groups. Their inherent hydrophilic properties result in poor waterproof performance and insufficient moisture resistance, which greatly limits the actual application scenarios and reliability of starch-based products.
[0003] Currently, the main methods for modifying the hydrophilicity defects of starch-based materials in the industry are divided into three categories: adding plasticizers to optimize processing performance, blending with hydrophobic components for modification, and surface hydrophobic modification of materials. By introducing hydrophobic systems, the surface hydrophilicity of the starch matrix is reduced, thereby improving the waterproof performance of the material.
[0004] Existing blending and surface modification technologies suffer from inherent core defects in material interface compatibility. The polar starch matrix and the hydrophobic modified components exhibit significant thermodynamic incompatibility, resulting in loose bonding and extremely poor interfacial compatibility between the two phases. This not only fails to achieve uniform and stable dispersion of the hydrophobic components but also causes problems such as interfacial peeling and water absorption in humid environments. Consequently, the waterproof and mechanical properties of the materials deteriorate rapidly and the stability is extremely poor. This makes it impossible to balance the biodegradability and long-term water resistance of starch-based materials, becoming a key technical bottleneck restricting the industrial application of high-performance starch-based biodegradable products.
[0005] Therefore, the present invention provides a method for preparing a starch-based biodegradable lunch box. Summary of the Invention
[0006] In order to overcome the shortcomings of the prior art, at least one technical problem raised in the background art is solved.
[0007] The technical solution adopted by this invention to solve its technical problem is: a method for preparing a starch-based biodegradable lunch box according to this invention, comprising the following steps:
[0008] Step 1: Raw material drying and precise moisture content control. The corn starch raw material is placed in a vacuum drying oven for continuous drying. The drying temperature is set at 75~85℃, the vacuum degree is controlled within the range of -0.08 to -0.09 MPa, and the drying time is set at 6~8 hours until the moisture content of the starch raw material is reduced to below 8%. The precise control of this moisture content index is based on the following technical considerations: If the moisture content is too high, it will cause water vapor flash evaporation during the subsequent thermoplastic processing, resulting in bubbles and microcracks inside the product, which will seriously weaken the mechanical strength and airtightness of the lunch box; if the moisture content is too low, the hydrogen bonds between starch molecules will be too tight, increasing the difficulty of plasticization and requiring a higher processing temperature to achieve sufficient starch gelatinization. However, a higher processing temperature will in turn exacerbate the risk of thermal degradation. In this step, the dried starch raw material is immediately transferred to a mixer with a sealed lid for temporary storage, awaiting subsequent batching.
[0009] Step 2: Construct and precisely proportion the heat-stabilizing synergistic system. Add a heat stabilizer composition to the mixer. This composition consists of three components: ascorbate palmitate, rosemary extract, and diatomaceous earth. Ascorbate palmitate acts as the main heat stabilizer, scavenging free radicals and effectively terminating the chain degradation process by binding with free radicals generated during starch thermal degradation. Rosemary extract is rich in caryopsisic acid and caryopsisol, which have excellent antioxidant properties and can inhibit oxidative degradation reactions during processing. Diatomaceous earth acts as a multifunctional filler, providing physical and chemical effects. The porous structure of the heat stabilizer acts as an insulator and heat dissipator, adsorbing some degradation products and reducing the local concentration of heat. In specific formulation practices, the mass ratios of the three components are precisely set as follows: 0.3-0.5 parts ascorbate palmitate, 0.2-0.4 parts rosemary extract, and 1.0-2.0 parts diatomaceous earth. Relative to 100 parts of starch raw material, this ratio range ensures the optimal balance between heat stabilization efficiency and food safety. After all heat stabilizer components are added, the mixer is thoroughly stirred and mixed at a speed of 60-80 rpm for 15-20 minutes to ensure that the heat stabilizer is evenly distributed in the starch powder.
[0010] Step 3: Prepare and add the plasticizer-coupling agent synergistic system. Add the plasticizer component and coupling agent component sequentially to the mixer. The plasticizer component is a combination of glycerol and sorbitol. Glycerol, as a small-molecule plasticizer, can quickly penetrate into the starch granules, disrupting the hydrogen bond network between starch molecules and lowering the glass transition temperature of starch. Sorbitol, as a large-molecule plasticizer, forms more stable hydrogen bonds with starch molecules, providing a sustained post-plasticizing effect and preventing plasticizer migration and volatilization. The coupling agent component is triethyl citrate. This coupling agent molecule contains both hydroxyl and ester functional groups. Its hydroxyl group can undergo esterification with the hydroxyl groups of starch molecules to form chemical bonds, and its ester group can interact with the starch molecule in the blend. The polylactic acid and other biodegradable plastics generate good intermolecular forces, thus building a flexible bridge at the interface between starch and biodegradable plastics, significantly improving the interfacial bonding strength between the two phases. In specific formulation practice, the mass ratio of glycerol to sorbitol in the plasticizer component is set in the range of 3:1 to 4:1, and the total addition amount is controlled at 15 to 20 parts. The addition amount of the coupling agent component is controlled between 2 and 4 parts. The addition process adopts a step-by-step drop-addition method. First, all the glycerol is added for pre-plasticization treatment for 5 to 8 minutes, and then a mixture of sorbitol and triethyl citrate is added for synergistic plasticization treatment for 10 to 15 minutes. The entire plasticizing process is carried out at a temperature of 40 to 50°C to ensure that the viscosity of the plasticizer is moderate and easy to penetrate and disperse.
[0011] Step 4: Preparation and granulation of starch-based biodegradable plastic blends. The plasticized mixture from the mixer is transferred to a twin-screw extruder for melt blending and granulation. The twin-screw extruder is configured with a three-section structure: a forward conveying section, a shearing and mixing section, and a melt homogenizing section. The forward conveying section uses equidistant deep-groove screw elements for stable material conveying and preheating. The shearing and mixing section uses cross-kneading block elements to provide strong shearing and dispersion, promoting uniform mixing of starch and biodegradable plastics. The melt homogenizing section uses reverse conveying screw elements to establish stable die head pressure. The extrusion processing temperature is precisely controlled by dividing the screw axis into five temperature zones: the feeding section temperature is set to 60-70℃, the plasticizing section temperature to 90-110℃, the mixing section temperature to 120-135℃, and the homogenizing section temperature... The temperature is set at 125~140℃, the die head temperature is set at 130~145℃, the screw speed is controlled within the range of 180~220 rpm, and the feeding speed is controlled within the range of 8~12 kg / h. In this step, the biodegradable plastic is a blend of polylactic acid and polybutylene adipate terephthalate, with the mass ratio of the two controlled within the range of 6:4 to 7:3. Polylactic acid provides good rigidity and biodegradability, while polybutylene adipate terephthalate provides excellent toughness and low-temperature processing performance. The mass ratio of starch to biodegradable plastic in the blend is set within the range of 45:55 to 50:50. The granulation process adopts underwater pelletizing, and the pelletizing speed is linked to the screw speed to ensure that the pellets are regular in shape and uniform in size. The resulting blended pellets have a diameter of 2~4 mm and a length of 3~6 mm.
[0012] Step 5: Perform lunchbox molding and post-processing. Transfer the blended granules obtained in Step 4 to an injection molding machine for lunchbox molding. The injection molding machine's barrel temperature is divided into three sections for gradient control: the rear section (130-145℃) for preheating and softening the granules, the middle section (140-155℃) for further homogenization of the melt, and the front section (150-165℃) to establish sufficient injection pressure. The mold temperature is set to 50-70℃ to ensure rapid product setting. The injection pressure is controlled within the range of 80-120 MPa, and the holding pressure is set to 6... The pressure ranges from 0 to 90 MPa, the holding time is set to 8 to 12 seconds, and the cooling time is set to 15 to 25 seconds. The injection-molded lunchbox blanks then enter the post-processing stage for curing and performance stabilization. The curing process is carried out in a constant temperature and humidity chamber, with the curing temperature set to 40 to 50°C, the relative humidity set to 30% to 40%, and the curing time set to 24 to 48 hours. The purpose of the curing process is to achieve a more uniform distribution of the plasticizer in the starch matrix, eliminate the internal stress generated during the molding process, and promote the orderly rearrangement of the starch crystallization zone, thereby comprehensively improving the dimensional stability and mechanical properties of the lunchbox.
[0013] Preferably, in the method for preparing a starch-based biodegradable lunch box according to the present invention, the particle size range of the diatomaceous earth component in the heat stabilizer composition is controlled between 5 and 15 micrometers. The determination of this particle size range is based on the following technical considerations: if the particle size of diatomaceous earth is too small, the specific surface area will be too large, which will easily adsorb too much plasticizer component, reduce the plasticizing efficiency and lead to an increase in the amount of plasticizer used; if the particle size of diatomaceous earth is too large, the dispersibility will be poor, which will easily form stress concentration points in the product and weaken the impact toughness of the lunch box. At the same time, the addition of diatomaceous earth can also give the product certain flame retardant and antibacterial properties. This is because the porous structure of diatomaceous earth can physically adsorb combustible gases and promote the formation of char layer. Its surface silanol groups have a strong adsorption and inhibition effect on Gram-positive bacteria.
[0014] Preferably, in the preparation method of a starch-based biodegradable lunch box provided by the present invention, the triethyl citrate of the coupling agent component needs to be preheated before addition. The preheating temperature is set at 35~45°C and the preheating time is 10~15 minutes. The purpose of the preheating treatment is to reduce the viscosity of triethyl citrate and improve its reactivity with starch molecules. During the esterification reaction, a catalyst needs to be added to promote the reaction. The catalyst is p-toluenesulfonic acid, and its addition amount is controlled within the range of 0.5% to 1.0% of the coupling agent mass. The addition of the catalyst can significantly reduce the activation energy of the esterification reaction, so that the reaction can be carried out under lower processing temperature conditions, avoiding excessive damage to the starch molecular chains by high temperature.
[0015] Preferably, in the method for preparing a starch-based biodegradable lunch box according to the present invention, the screw length-to-diameter ratio of the twin-screw extruder is set to a range of 48:1 to 52:1. A larger length-to-diameter ratio can provide a longer melt mixing path, which is beneficial to the full contact and uniform dispersion of starch and biodegradable plastic. At the same time, it can establish a more stable die head pressure, which is beneficial to improving the quality stability of the granules. A vacuum devolatilization and degassing device is also provided in the shearing and mixing section. The vacuum degree of the degassing zone is controlled in the range of -0.06 to -0.08 MPa. This device can effectively remove water vapor and small molecule volatile substances generated during the blending process, reduce bubble defects in the product, and improve the utilization efficiency of heat stabilizers.
[0016] Preferably, in the preparation method of a starch-based biodegradable lunch box provided by the present invention, in the injection molding process, the mold design adopts a multi-cavity hot runner system to improve production efficiency and ensure product quality consistency. The hot runner temperature is precisely controlled within the range of 155~165℃, and the temperature fluctuation is controlled within ±2℃. The orifice diameter of the hot runner nozzle is designed to be 0.8~1.2 mm to ensure the uniformity of melt flow rate. The runner system of the lunch box mold adopts a balanced arrangement, and the runner length and cross-sectional area of each cavity are kept consistent to ensure that the melt filling state of each lunch box is the same. The cooling system of the mold adopts a conformal cooling water channel design, the cooling water flow rate is controlled within the range of 1.5~2.5 m / s, and the cooling water temperature is controlled within the range of 20~25℃. Precise cooling control can eliminate product warping deformation to the greatest extent and shorten the molding cycle.
[0017] Preferably, in the preparation method of a starch-based biodegradable lunch box provided by the present invention, humidity control in the post-processing curing step is a key process parameter. The relative humidity is controlled within the range of 30% to 40% to prevent the reabsorption of plasticizer in the lunch box under high humidity. If the relative humidity is too high, the moisture in the air will be adsorbed by the starch, which will break the hydrogen bond competition balance between starch and plasticizer, causing starch retrogradation and deterioration of product performance. If the relative humidity is too low, the plasticizer will migrate and accumulate on the surface of the product, affecting the appearance quality and performance of the product. After curing, the lunch box needs to be tested for moisture content. The moisture content should be controlled within the range of 1% to 2%. If the moisture content is too high, the curing time needs to be extended. If the moisture content is too low, moisture-proof measures need to be taken in the subsequent packaging process.
[0018] Preferably, the technical mechanism of the starch-based biodegradable lunch box preparation method of the present invention follows the following logic during application:
[0019] During the raw material drying stage, precisely controlling the moisture content to below 8% avoids product defects caused by water flash evaporation while retaining sufficient moisture for subsequent plasticizing reactions, creating favorable conditions for starch gelatinization. In the thermal stability system construction stage, ascorbate palmitate and rosemary extract form a synergistic antioxidant system, simultaneously inhibiting thermal degradation reactions from both free radical scavenging and oxidative chain termination perspectives. The addition of diatomaceous earth provides physical thermal dispersion and adsorption isolation functions. The synergistic effect of these three components effectively increases the thermal decomposition temperature of starch.
[0020] During the plasticizing coupling stage, the combined use of glycerol and sorbitol achieved the dual effects of rapid plasticization and sustained post-plasticization. The interfacial coupling effect of triethyl citrate significantly improved the compatibility between starch and polylactic acid.
[0021] During the blending and granulation stage, precise temperature control and aspect ratio optimization of the twin-screw extruder ensured thorough plasticization of the starch and uniform dispersion of the blend.
[0022] During the molding and curing stage, gradient temperature control and constant temperature and humidity curing treatment ensured the dimensional stability and overall performance improvement of the products.
[0023] The beneficial effects of this invention are as follows:
[0024] 1. The present invention discloses a method for preparing a starch-based biodegradable lunch box. By constructing a ternary thermally stable synergistic system, the present invention fundamentally changes the thermal degradation behavior of starch-based materials during thermoplastic processing. In traditional methods, starch exhibits obvious discoloration and molecular chain breakage at a processing temperature of 130-140℃. However, the method of the present invention can maintain the integrity of starch molecular chains at a processing temperature of 145-155℃, reducing the thermal degradation rate by more than 60%. This allows the starch filling amount to be increased to 45%-50% while maintaining the biodegradability of the product, which is 10-15 percentage points higher than the traditional method. This effectively reduces the amount of biodegradable plastic used, thereby reducing raw material costs and improving the environmental performance of the product.
[0025] 2. The present invention discloses a method for preparing a starch-based biodegradable lunch box. Through a dual regulatory mechanism of plasticizer compounding and interfacial coupling, the present invention significantly improves the interfacial bonding state between starch and biodegradable plastic. Scanning electron microscopy observations show that in the blend prepared by the method of the present invention, the phase interface between the starch phase and the polylactic acid phase is blurred and tightly bonded. The phase domain size is reduced from 5-10 micrometers in the traditional method to 1-3 micrometers. The improved interfacial bonding strength is directly reflected in the mechanical properties of the product. The prepared lunch box achieves a flexural strength of 35-45 MPa and an impact strength of 8-12 kJ / m², which are more than 30% and 50% higher than those prepared by the traditional method, respectively. Furthermore, in an accelerated aging test at 25°C and 85% relative humidity, the mechanical properties of the product are retained at over 85% after 168 hours, effectively solving the industry pain point of rapid performance degradation in humid environments in existing technologies.
[0026] 3. The method for preparing a starch-based biodegradable lunch box according to the present invention ensures the consistency of product quality between batches through a precise control system of process parameters throughout the entire process. Key control points in the production process include raw material moisture content, heat stabilizer ratio, extrusion temperature gradient, injection molding process parameters, and curing environment conditions. Each control point has a clearly defined range of technical indicators and online monitoring methods. Statistical process control data show that the batch variation coefficients of the main performance indicators of the product, such as density, tensile strength, flexural modulus, and biodegradability, are all controlled within 5%, meeting the stringent requirements for quality stability in large-scale industrial production and laying a solid foundation for the industrial application of starch-based biodegradable lunch boxes. Attached Figure Description
[0027] The invention will now be further described with reference to the accompanying drawings.
[0028] Figure 1 This is a flowchart of a method for preparing a starch-based biodegradable lunch box according to the present invention;
[0029] Figure 2 This is a flowchart illustrating the preparation of starch-based blends and the process of forming lunch boxes in this invention. Detailed Implementation
[0030] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.
[0031] Example 1: As Figure 1 and Figure 2 As shown, this embodiment relates to a method for preparing a starch-based biodegradable lunch box, which includes the following steps:
[0032] In step one, the raw material drying and precise moisture content control processes form the basic prerequisites for the entire preparation process.
[0033] The corn starch raw material was placed in a vacuum drying oven for continuous drying. The drying temperature was set at 75~85℃, the vacuum degree was controlled within the range of -0.08 to -0.09 MPa, and the drying time was set at 6~8 hours until the moisture content of the starch raw material was reduced to below 8%.
[0034] The precise control of this moisture content index is based on the following technical mechanism: if the moisture content is too high, it will cause water vapor flash evaporation during the later thermoplastic processing, resulting in bubbles and microcracks inside the product, which will seriously weaken the mechanical strength and airtightness of the lunch box; if the moisture content is too low, the hydrogen bonds between starch molecules will be too tight, increasing the difficulty of plasticization and requiring higher processing temperatures to achieve sufficient starch gelatinization. However, higher processing temperatures will in turn exacerbate the risk of thermal degradation.
[0035] In this step, the dried starch raw material is immediately transferred to a mixer with a sealed cover for temporary storage, awaiting subsequent batching.
[0036] The sealing performance of the mixer is ensured by a double-layer silicone sealing ring structure. The effective compression of the sealing ring is set to 2.5~3.0 mm to eliminate the risk of environmental moisture intrusion during operation downtime.
[0037] In step two, the process of constructing and precisely proportioning the thermally stable synergistic system involves adding the thermal stabilizer composition into the mixer.
[0038] The heat stabilizer composition consists of three components: ascorbate palmitate, rosemary extract, and diatomaceous earth.
[0039] Ascorbate palmitate acts as the main heat stabilizer and plays a free radical scavenging role. It can combine with free radicals generated by the thermal degradation of starch and effectively terminate the chain degradation process.
[0040] Rosemary extract contains abundant caryopsisic acid and caryopsisol, which have good antioxidant properties and can inhibit oxidative degradation reactions during processing. The rosemary extract is prepared by ethanol reflux extraction, wherein the mass content of caryopsisic acid is ≥20% and the mass content of caryopsisol is ≥5%.
[0041] Diatomaceous earth serves as a multifunctional filler, providing physical insulation and heat dissipation. Its porous structure can adsorb some degradation products and reduce the local concentration of heat.
[0042] In specific formulation practice, the mass ratios of the three components are precisely set as follows: 0.3-0.5 parts ascorbyl palmitate, 0.2-0.4 parts rosemary extract, and 1.0-2.0 parts diatomaceous earth. Relative to 100 parts of starch raw material, this ratio range ensures the optimal balance between heat stability efficiency and food safety. After all heat stabilizer components are added, the mixer is thoroughly stirred and mixed at a speed of 60-80 rpm for 15-20 minutes to ensure that the heat stabilizer is evenly distributed in the starch powder.
[0043] In a preferred embodiment of this step, the particle size range of the diatomaceous earth component in the heat stabilizer composition is controlled between 5 and 15 micrometers.
[0044] If the particle size of diatomaceous earth is too small, the specific surface area will be too large, which will easily adsorb too much plasticizer components, reduce the plasticizing efficiency and lead to an increase in the amount of plasticizer used; if the particle size of diatomaceous earth is too large, the dispersibility will be poor, which will easily form stress concentration points in the product and weaken the impact toughness of the lunch box.
[0045] The porous structure of diatomaceous earth endows products with additional functional properties. Its porous structure can physically adsorb flammable gases and promote the formation of char layer, thus giving it certain flame retardant properties. The silanol groups on its surface have a strong adsorption and inhibition effect on Gram-positive bacteria, thus giving it certain antibacterial properties.
[0046] In step three, the plasticizer-coupling agent synergistic system is prepared and added by sequentially adding the plasticizer component and the coupling agent component into the mixer.
[0047] The plasticizer component is a combination of glycerol and sorbitol. Glycerol, as a small molecule plasticizer, can quickly penetrate into the starch granules, disrupt the hydrogen bond network between starch molecules, and lower the glass transition temperature of starch. Sorbitol, as a large molecule plasticizer, forms a more stable hydrogen bond with starch molecules, providing a sustained post-plasticizing effect and preventing the plasticizer from migrating out and volatilizing.
[0048] The coupling agent component is triethyl citrate. The coupling agent molecule contains both hydroxyl and ester functional groups. Its hydroxyl group can undergo esterification with the hydroxyl group of starch molecule to form a chemical bond, and its ester group can generate good intermolecular forces with biodegradable plastics such as polylactic acid in the blend system. This creates a flexible bridge at the interface between starch and biodegradable plastic, significantly improving the interfacial bonding strength between the two phases.
[0049] In specific formulation practices, the mass ratio of glycerol to sorbitol in the plasticizer component is set to a range of 3:1 to 4:1, with the total addition amount controlled at 15 to 20 parts, and the addition amount of the coupling agent component is controlled at 2 to 4 parts.
[0050] The addition process adopts a step-by-step dripping method. First, all the glycerin is added for pre-plasticization treatment for 5-8 minutes, and then a mixture of sorbitol and triethyl citrate is added for synergistic plasticization treatment for 10-15 minutes.
[0051] The entire plasticizing process is carried out at a temperature of 40~50℃ to ensure that the plasticizer has a moderate viscosity and is easy to penetrate and disperse.
[0052] The esterification reaction of triethyl citrate and starch is carried out in situ under the high temperature and shearing environment of twin-screw extrusion. The degree of reaction is controlled by the extrusion residence time and temperature. The residence time of the material in the shearing and mixing section is controlled to be 40-60 seconds to ensure that the esterification reaction conversion rate reaches more than 30%. Unreacted triethyl citrate remains in the system as an auxiliary plasticizer.
[0053] As a preferred embodiment of this step, the triethyl citrate of the coupling agent component needs to be preheated before being added. The preheating temperature is set to 35~45°C and the preheating time is 10~15 minutes.
[0054] The purpose of preheating is to reduce the viscosity of triethyl citrate and increase its reactivity with starch molecules. A catalyst is required during the esterification process to promote the reaction. The catalyst is p-toluenesulfonic acid, and its addition amount is controlled within the range of 0.5% to 1.0% of the coupling agent mass.
[0055] The addition of a catalyst can significantly reduce the activation energy of the esterification reaction, allowing the reaction to proceed at a lower processing temperature, thus avoiding excessive damage to the starch molecular chains caused by high temperatures.
[0056] In step four, the preparation and granulation process of starch-based biodegradable plastic blends involves transferring the plasticized mixture from the mixer to a twin-screw extruder for melt blending and granulation.
[0057] The screw configuration of the twin-screw extruder is configured as a three-section structure consisting of a forward conveying section, a shearing and mixing section, and a melt homogenization section.
[0058] The forward conveying section uses equidistant deep groove screw elements for stable material conveying and preheating, the shearing and mixing section uses cross kneading block elements to provide strong shearing and dispersing action, promoting uniform mixing of starch and biodegradable plastics, and the melt homogenization section uses reverse conveying screw elements to establish stable die head pressure.
[0059] The extrusion processing temperature is precisely controlled by dividing it into five temperature zones along the screw axis: the feeding zone temperature is set at 60~70℃, the plasticizing zone temperature is set at 90~110℃, the mixing zone temperature is set at 120~135℃, the homogenizing zone temperature is set at 125~140℃, and the die head temperature is set at 130~145℃.
[0060] The screw speed is controlled within the range of 180~220 revolutions per minute, and the feeding speed is controlled within the range of 8~12 kilograms per hour.
[0061] In this step, the biodegradable plastic is a blend of polylactic acid and polybutylene adipate terephthalate, with the mass ratio of the two controlled within the range of 6:4 to 7:3.
[0062] Polylactic acid (PLA) offers good rigidity and biodegradability, while polybutylene adipate (PEG) offers excellent toughness and low-temperature processing properties.
[0063] The mass ratio of starch to biodegradable plastic in the blend was set to be in the range of 45:55 to 50:50.
[0064] The pelletizing process uses underwater pelletizing, with the pelletizing speed and screw rotation speed being linked for control, ensuring that the pellets are regular in shape and uniform in size, resulting in blended pellets with a diameter of 2-4 mm and a length of 3-6 mm.
[0065] As a preferred embodiment of this step, the screw length-to-diameter ratio of the twin-screw extruder is set to a range of 48:1 to 52:1.
[0066] A larger aspect ratio provides a longer melt mixing path, which is beneficial for the full contact and uniform dispersion of starch and biodegradable plastics. At the same time, it can establish a more stable die head pressure, which is beneficial for improving the quality stability of the pellets.
[0067] A vacuum degassing device is also installed in the shearing and mixing section. The vacuum level in the exhaust zone is controlled within the range of -0.06 to -0.08 MPa. This device can effectively remove water vapor and small molecule volatile substances generated during the blending process, reduce bubble defects in the product, and improve the utilization efficiency of heat stabilizers.
[0068] In step five, the lunchbox molding and post-processing process transfers the blended granules obtained in step four to an injection molding machine for lunchbox molding.
[0069] The barrel temperature of the injection molding machine is divided into three sections for gradient control: the rear section temperature is set at 130~145℃ for preheating and softening the granules, the middle section temperature is set at 140~155℃ for further homogenization of the melt, and the front section temperature is set at 150~165℃ to establish sufficient injection pressure.
[0070] The mold temperature is set to 50~70℃ to ensure rapid product shaping, the injection pressure is controlled within the range of 80~120 MPa, the holding pressure is set to 60~90 MPa, the holding time is configured to 8~12 seconds, and the cooling time is configured to 15~25 seconds. The injection-molded lunch box blank then enters the post-processing process for curing and performance stabilization.
[0071] The post-treatment curing was carried out in a constant temperature and humidity chamber, with the curing temperature set at 40~50℃, the relative humidity set at 30%~40%, and the curing time set at 24~48 hours.
[0072] The purpose of the curing process is to achieve a more uniform distribution of plasticizer in the starch matrix, eliminate internal stress generated during molding, and promote the orderly rearrangement of starch crystallization zones, thereby comprehensively improving the dimensional stability and mechanical properties of the lunch box.
[0073] As a preferred embodiment of this step, in the injection molding process, the mold design adopts a multi-cavity hot runner system to improve production efficiency and ensure product quality consistency.
[0074] The hot runner temperature is precisely controlled within the range of 155~165℃, with temperature fluctuations controlled within ±2℃. The orifice diameter of the hot runner nozzle is designed to be 0.8~1.2 mm to ensure the uniformity of melt flow rate.
[0075] The runner system of the lunch box mold adopts a balanced arrangement, and the runner length and cross-sectional area of each cavity are kept consistent to ensure that the melt filling state of each lunch box is the same.
[0076] The mold's cooling system adopts a conformal cooling water channel design. The flow rate of the cooling water is controlled within the range of 1.5 to 2.5 meters per second, and the cooling water temperature is controlled within the range of 20 to 25 degrees Celsius. Precise cooling control can eliminate warping deformation of the product to the greatest extent and shorten the molding cycle.
[0077] In another preferred embodiment of this step, humidity control in the post-processing curing process is a key process parameter.
[0078] The relative humidity is controlled within the range of 30% to 40% to prevent the plasticizer from being absorbed back into the food container in a high humidity environment.
[0079] If the relative humidity is too high, the moisture in the air will be absorbed by the starch, which will break the competitive balance of hydrogen bonds between starch and plasticizer, causing starch retrogradation and deterioration of product performance; if the relative humidity is too low, the plasticizer will migrate and accumulate on the surface of the product, affecting the appearance quality and performance of the product.
[0080] After the food containers have been cooked, their moisture content needs to be tested. The moisture content should be controlled within the range of 1% to 2%. If the moisture content is too high, the cooking time needs to be extended. If the moisture content is too low, moisture-proof measures need to be taken in the subsequent packaging process.
[0081] The technical solution of this embodiment will be further explained through specific application examples below.
[0082] Taking the preparation of a rectangular lunchbox with a capacity of 500 ml as an example, the specific operation process and key parameter settings are as follows.
[0083] In the raw material pretreatment stage, 100 kg of corn starch raw material was selected and placed in a vacuum drying oven for continuous drying.
[0084] The working vacuum degree of the vacuum drying oven was set to -0.085 MPa, the heating temperature was set to 80℃, and the drying time was 7 hours.
[0085] During the drying process, the starch raw material is sampled and tested every 2 hours, and the moisture content is measured using a Karl Fischer moisture analyzer. The drying process is complete when the moisture content drops to 7.5%. The dried starch raw material is then transferred to a mixer for temporary storage via a closed conveyor pipeline.
[0086] The mixer is made of stainless steel and has a capacity of 200 liters. It is equipped with a dual-speed mixing system. The low-speed mixing speed is 40 revolutions per minute for adding and mixing materials, and the high-speed mixing speed is 70 revolutions per minute for uniform dispersion.
[0087] During the heat stabilizer addition stage, 0.4 kg of ascorbate palmitate, 0.3 kg of rosemary extract, and 1.5 kg of diatomaceous earth were added sequentially to the mixer.
[0088] The particle size of diatomaceous earth was measured by a Malvern laser particle size analyzer. Its D50 particle size was 10 micrometers and its D90 particle size was 15 micrometers, which meets the particle size control requirements of 5 to 15 micrometers.
[0089] After the three heat stabilizer components are added, the mixer is stirred and mixed at a speed of 70 rpm for 18 minutes to ensure that the heat stabilizer is evenly distributed in the starch powder.
[0090] The uniformity of mixing is tested using a sampling analysis method. Five samples are taken from different locations in the mixer, and the content of heat stabilizer is determined. The coefficient of variation is considered to be within 3% to be qualified.
[0091] In the plasticizer-coupling agent addition process, 4.5 kg of glycerin is first added to the mixer. The jacket of the mixer is heated and kept warm by circulating water at 45°C. The pre-plasticization treatment of glycerin lasts for 7 minutes.
[0092] During the preplasticization process, glycerol rapidly penetrates into the starch granules and forms hydrogen bonds with the hydroxyl groups in the starch molecules, thus beginning to disrupt the hydrogen bond network between starch molecules.
[0093] Then, 1.5 kg of sorbitol was mixed evenly with 3 kg of triethyl citrate preheated to 40°C to form a synergistic plasticizing mixture. This mixture was then slowly added to the mixer via a dripping device, with the dripping time controlled at 12 minutes. The sorbitol molecules and glycerol molecules worked synergistically to further disrupt the crystalline regions of starch and increase the degree of amorphization of starch.
[0094] Under the promotion of the p-toluenesulfonic acid catalyst (30 g added), the hydroxyl groups of triethyl citrate begin to undergo an esterification reaction with the hydroxyl groups of starch molecules, forming chemical bonds. After the synergistic plasticization treatment is completed, the mixture is kept warm and stirred for another 5 minutes to ensure that the esterification reaction is fully carried out.
[0095] The entire plasticizing process is carried out at a circulating water temperature of 45°C in the mixer jacket to ensure that the plasticizer has a suitable viscosity and is easy to penetrate and disperse.
[0096] In the blending and granulation stage, the plasticized mixture is transferred to a twin-screw extruder for melt blending and granulation. The twin-screw extruder has a screw diameter of 47 mm, a length-to-diameter ratio of 50:1, and is equipped with 5 heating zones and 1 cooling zone.
[0097] The biodegradable plastic is a blend of polylactic acid and polybutylene terephthalate (PET), with polylactic acid having a melt index of 25 g / 10 min and PET having a melt index of 18 g / 10 min.
[0098] The two biodegradable plastics were first premixed in a high-speed mixer, with the mass ratio of polylactic acid to polybutylene adipate set at 65:35.
[0099] The mass ratio of starch to biodegradable plastic in the mixture is set to 48:52. The temperature parameters of the extruder are configured as follows: feeding section temperature is 65℃, plasticizing section temperature is 100℃, mixing section temperature is 130℃, homogenizing section temperature is 135℃, and die head temperature is 140℃.
[0100] The screw speed is set to 200 rpm, and the feeding speed is set to 10 kg / h. A vacuum devolatilization exhaust device is installed in the shearing and mixing section, and the exhaust vacuum degree is controlled at -0.07 MPa.
[0101] The pelletizing process adopts underwater pelletizing, with the pelletizing water temperature controlled at 30~35℃, and the linkage ratio between pelletizing speed and screw speed set at 1:15.
[0102] The resulting blended granules, after sieving, had a diameter of 3 mm, a length of 4.5 mm, a bulk density of 0.95 g / cm³, and a moisture content of 0.8% as determined by an infrared moisture meter.
[0103] During the injection molding stage, the blended granules are transferred to the injection molding machine for the molding of the lunch box. The clamping force of the injection molding machine is 650 tons, and the barrel adopts a three-stage temperature control: the rear temperature is 135℃, the middle temperature is 148℃, and the front temperature is 158℃.
[0104] The mold adopts a multi-cavity hot runner system with a configuration of 4 cavities. The external dimensions of the lunch box are 180 mm in length, 130 mm in width, and 35 mm in height.
[0105] The hot runner temperature is set at 160℃, with temperature fluctuations controlled within ±1.5℃. The hot runner nozzle orifice diameter is designed to be 1.0 mm.
[0106] The mold's cooling system adopts a conformal cooling water channel design, with the cooling water temperature controlled at 22℃ and the cooling water flow rate controlled at 2.0 meters per second.
[0107] The injection molding process parameters are configured as follows: injection pressure is 95 MPa, holding pressure is 75 MPa, holding time is 10 seconds, cooling time is 20 seconds, molding cycle is 35 seconds, and the molded lunch box blank is inspected by a visual inspection system and has no defects such as bubbles, flash, or shrinkage marks on the surface.
[0108] In the post-processing curing stage, the injection-molded lunch box blanks are neatly stacked in a turnover box and transferred to a constant temperature and humidity chamber for curing treatment.
[0109] The temperature of the curing chamber was set at 45℃, the relative humidity was set at 35%, and the curing time was 36 hours. During the curing process, samples of the lunch boxes were taken every 12 hours to measure their mechanical properties and dimensional changes.
[0110] After maturation, the moisture content of the lunch box was measured to be 1.5% by an infrared moisture meter, which meets the control requirement of 1%~2%. The dimensional stability of the lunch box was tested, and the change rate in the length direction was 0.12%, the change rate in the width direction was 0.08%, and the change rate in the height direction was 0.15%, all of which meet the design requirements.
[0111] The final product performance test results are as follows: the density of the lunch box was measured to be 1.18 grams per cubic centimeter, the tensile strength was 28 MPa, the flexural strength was 42 MPa, and the impact strength was 10.5 kJ per square meter.
[0112] The biodegradability rate was 72% after a 28-day home composting degradation test, which meets the requirement of not less than 60% in the GB / T18006.3-2020 standard.
[0113] In an accelerated aging test at 25°C and 85% relative humidity, the product retained 87% of its tensile strength, 86% of its flexural strength, and 84% of its impact strength after 168 hours, demonstrating excellent aging resistance.
[0114] Example 2: This example provides an alternative technical solution for the preparation method of starch-based biodegradable lunch boxes. While keeping the core process unchanged, this solution makes adaptive adjustments to some process parameters and technical details to meet the production needs of different product specifications and performance requirements.
[0115] In terms of raw material selection, this embodiment uses cassava starch as the main starch raw material. Cassava starch and corn starch are similar in molecular structure, both being a mixture of amylose and amylopectin. However, cassava starch has a slightly higher amylose content, about 17% to 20%, while corn starch has an amylose content of about 25% to 28%.
[0116] This characteristic of cassava starch gives it better film-forming properties and a lower gelatinization temperature, which is beneficial for achieving full plasticization at lower processing temperatures.
[0117] During the raw material drying stage, the drying temperature of cassava starch is set at 70~80℃, which is about 5℃ lower than the drying temperature of corn starch.
[0118] This is because cassava starch has a relatively loose granular structure and low resistance to internal moisture migration. Excessively high drying temperatures can easily cause the granule surface to harden, affecting the subsequent plasticizing and penetrating effect.
[0119] The vacuum level is maintained within the range of -0.08 to -0.09 MPa, the drying time is set to 5 to 7 hours, and the moisture content is controlled to be below 8%.
[0120] Regarding the heat stabilizer formulation, considering that the chemical activity of cassava starch is slightly lower than that of corn starch, the heat stabilizer formulation has been adjusted accordingly. The amount of ascorbate palmitate added has been adjusted to 0.4~0.6 parts, the amount of rosemary extract added has been adjusted to 0.3~0.5 parts, and the amount of diatomaceous earth added has been kept at 1.0~2.0 parts.
[0121] A higher amount of heat stabilizer can compensate for the differences in the thermal stability of cassava starch, ensuring sufficient thermal stability during subsequent thermoplastic processing.
[0122] In the plasticizer-coupling agent system, the gelatinization temperature of cassava starch is about 58~65℃, which is 5~10℃ lower than that of corn starch. Therefore, the parameters of the plasticizer system need to be adjusted accordingly.
[0123] The mass ratio of glycerol to sorbitol was adjusted to a range of 2.5:1 to 3.5:1, and the total amount added was controlled between 14 and 18 parts. A lower glycerol ratio helps to control the total amount of plasticizer and avoid the decline in mechanical properties caused by over-plasticization.
[0124] The temperature of the plasticizing process is controlled at 38~48℃, which is about 2℃ lower than that of Example 1, in order to adapt to the lower heat softening temperature of cassava starch. The amount of triethyl citrate added is maintained at 2~4 parts, and the amount of catalyst p-toluenesulfonic acid added is controlled at 0.6%~1.0% of the coupling agent mass.
[0125] During the blending and granulation stage, the temperature parameters of the twin-screw extruder were optimized and adjusted: the feeding section temperature was 55~65℃, the plasticizing section temperature was 85~105℃, the mixing section temperature was 115~130℃, the homogenizing section temperature was 120~135℃, and the die head temperature was 125~140℃.
[0126] The overall temperature was reduced by 5-10°C compared to Example 1 to accommodate the lower processing temperature window of cassava starch. In the formulation of biodegradable plastic, the mass ratio of polylactic acid to polybutylene adipate was adjusted to a range of 7:3 to 6.5:3.5 to improve the rigidity of the product and meet the stacking and load-bearing requirements of the lunch box during use.
[0127] The mass ratio of starch to biodegradable plastic is adjusted to 50:50 to obtain a higher starch content and reduce the cost of using biodegradable plastic. The screw speed is set to 160~200 rpm and the feeding speed is set to 9~11 kg per hour.
[0128] During the injection molding stage, the barrel temperature is set to 125~140℃ for the rear section, 135~150℃ for the middle section, and 145~160℃ for the front section.
[0129] The mold temperature is set at 45~65℃ to accommodate the rapid solidification characteristics of cassava starch-based materials.
[0130] The injection pressure is set to 75~110 MPa, the holding pressure to 55~85 MPa, the holding time to 7~11 seconds, and the cooling time to 13~23 seconds. The hot runner temperature is set to 150~160℃ to ensure that the viscosity of the melt in the hot runner is appropriate, avoiding blockage of cold material due to excessively low temperature or decomposition of the melt due to excessively high temperature.
[0131] Regarding product specifications, this embodiment takes a round lunchbox with a capacity of 250 ml as an example for illustration. The lunchbox has an external dimension of 120 mm in diameter, 30 mm in height, and a wall thickness of 2.5 mm.
[0132] The mold runner system for round lunch boxes adopts a center gate design with a runner length of 45 mm and a runner cross-sectional area of 28 square millimeters, ensuring that the melt enters the cavity through the shortest path, reducing pressure loss and temperature drop.
[0133] The cooling system uses three sets of concentric cooling water channels. The inner channel has a diameter of 40 mm and the outer channel has a diameter of 100 mm. The cooling water temperature is controlled at 20~23℃ and the cooling water flow rate is controlled at 1.8~2.2 meters per second.
[0134] In the post-processing curing stage, the curing temperature is set at 38~48℃, the relative humidity is set at 32%~38%, and the curing time is 30~42 hours.
[0135] Lower cooking temperatures and relative humidity help control the moisture content of cassava starch-based food containers, preventing excessive softening due to the strong water absorption of cassava starch.
[0136] The performance test results of the cassava starch-based lunch box prepared in this embodiment are as follows: density is 1.15 g / cm³, tensile strength is 26 MPa, flexural strength is 40 MPa, and impact strength is 9.8 kJ / m².
[0137] The biodegradability rate is 75%, and the 28-day composting degradation test shows that the product can be completely degraded. In terms of aging resistance, in the accelerated aging test at 25°C and 85% relative humidity, the mechanical property retention rate after 168 hours is comparable to that of Example 1, both remaining above 85%.
[0138] Comparative Examples: To verify the technical effect of the present invention, the following comparative examples are set for comparative analysis.
[0139] Comparative Example 1 uses the traditional method for preparing starch-based lunch boxes, without adding a heat stabilizer composition, and only uses glycerin as a plasticizer.
[0140] The specific operation is as follows: the corn starch raw material is dried in an atmospheric pressure oven at a temperature of 70°C for 8 hours, and the moisture content is controlled at 9%.
[0141] 18 parts of glycerol were added to the dried starch, without adding sorbitol, triethyl citrate, or other heat stabilizers. The mixture was melt-blended in a twin-screw extruder with the following extrusion temperatures set: 60°C in the feeding section, 90°C in the plasticizing section, 120°C in the mixing section, 125°C in the homogenizing section, and 130°C in the die head. The screw speed was 180 rpm. Polylactic acid was used as the biodegradable plastic, and the mass ratio of starch to polylactic acid was 35:65.
[0142] The injection molding temperature is set to 130℃ for the rear section, 140℃ for the middle section, and 150℃ for the front section. The mold temperature is 55℃. After molding, the performance is tested directly without post-processing curing.
[0143] Comparative Example 2 uses a conventional heat stabilizer modification method, using phosphite heat stabilizers to replace the ternary heat-stabilizing synergistic system of the present invention.
[0144] The specific operation is as follows: The drying treatment of corn starch raw material is the same as in Example 1. The heat stabilizer is a phosphite heat stabilizer, and the addition amount is 1.5 parts. Ascorbate palmitate, rosemary extract and diatomaceous earth are not added.
[0145] The plasticizing system uses a combination of glycerol and sorbitol in a mass ratio of 3:1, with a total addition of 16 parts. Triethyl citrate coupling agent is not added. Other process parameters are the same as in Example 1. The molded food containers undergo post-treatment curing under the same conditions as in Example 1.
[0146] Table 1: Comparison of Embodiments of the Invention with Comparative Examples
[0147] Performance indicators Example 1 Example 2 Comparative Example 1 Comparative Example 2 Starch filling amount / % 48 50 35 45 Tensile strength / MPa 28 26 18 23 Bending strength / MPa 42 40 26 33 Impact strength (kJ / m²) 10.5 9.8 5.2 7.8 Biodegradation rate / % 72 75 58 65 Thermal degradation rate / % 8 9 28 18 aging resistance retention rate / % 87 86 52 68 Processing temperature range / °C 130~145 125~140 120~130 125~135
[0148] The data in the comparison table show that the embodiments of the present invention are significantly better than the comparative schemes in all performance indicators.
[0149] The starch filling amount of Example 1 reached 48%, which is 13 percentage points higher than that of Comparative Example 1 (35%) and 3 percentage points higher than that of Comparative Example 2 (45%). This shows that the ternary thermally stable synergistic system of the present invention effectively expands the thermoplastic processing window, making it possible to have a higher starch filling amount.
[0150] In terms of mechanical properties, the bending strength of Example 1 reached 42 MPa, which was 61.5% higher than that of Comparative Example 1 (26 MPa) and 27.3% higher than that of Comparative Example 2 (33 MPa); the impact strength reached 10.5 kJ / m², which was 102% higher than that of Comparative Example 1 (5.2 kJ / m²) and 34.6% higher than that of Comparative Example 2 (7.8 kJ / m²).
[0151] The synergistic effect of interfacial coupling and plasticizer compound system significantly improved the compatibility between starch and biodegradable plastics, resulting in a comprehensive improvement in mechanical properties.
[0152] Regarding thermal degradation control, the thermal degradation rate of Example 1 was only 8%, which was 71.4% lower than that of Comparative Example 1 (28%) and 55.6% lower than that of Comparative Example 2 (18%), fully demonstrating the high efficiency of the ternary thermally stable synergistic system in inhibiting starch thermal degradation.
[0153] Regarding aging resistance, the performance retention rate of Example 1 after accelerated aging test was 87%, which is 67.3% higher than that of Comparative Example 1 (52%) and 27.9% higher than that of Comparative Example 2 (68%), indicating that the lunch box prepared by the technical solution of the present invention has excellent long-term reliability.
[0154] In terms of biodegradation rate, Examples 1 and 2 reached 72% and 75% respectively, both of which meet the requirements of GB / T18006.3-2020 standard. This is a significant improvement compared to 58% in Comparative Example 1 and 65% in Comparative Example 2, demonstrating higher environmental performance.
[0155] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a starch-based biodegradable lunch box, comprising the following steps: Step 1: Vacuum dry the starch raw material to obtain a dry starch raw material with a moisture content lower than the preset value; Step 2: Add a heat stabilizer composition to the dried starch raw material in the mixer. The heat stabilizer composition contains ascorbyl palmitate, rosemary extract and diatomaceous earth. After mixing evenly, heat stabilized starch is obtained. Step 3: Add plasticizer components and coupling agent components to the heat-stabilized starch. The plasticizer components include glycerol and sorbitol, and the coupling agent components include triethyl citrate. After mixing evenly, a plasticized mixture is obtained. Step 4: Transfer the plasticized mixture to a twin-screw extruder for melt blending and granulation to obtain starch-based biodegradable plastic blend granules; Step 5: Transfer the blended granules to an injection molding machine for lunchbox molding to obtain a lunchbox blank; Step 6: Perform a curing treatment on the lunchbox blank to obtain a starch-based biodegradable lunchbox.
2. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, In the vacuum drying process, the drying temperature is set within a preset range, the vacuum degree is controlled within a preset range, and the drying time is configured to a preset value; the dried starch raw material is transferred to a mixer with a sealed cover for temporary storage.
3. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The particle size range of the diatomaceous earth component in the heat stabilizer composition is controlled within a preset range.
4. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The triethyl citrate component of the coupling agent is preheated before being added; after preheating, a catalyst is added to promote the esterification reaction.
5. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The plasticizer component is added in a stepwise manner. First, all the glycerol is added for pre-plasticization, and then a mixture of sorbitol and triethyl citrate is added for synergistic plasticization.
6. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The triethyl citrate reacts with starch via esterification through hydroxyl groups and forms intermolecular forces with biodegradable plastics through ester groups, thus forming chemical bonds at the interface between the two phases.
7. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The screw length-to-diameter ratio of the twin-screw extruder is set within a preset range; a vacuum devolatilization and degassing device is installed in the shearing and mixing section.
8. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The screw configuration of the twin-screw extruder includes a forward conveying section, a shearing and mixing section, and a melt homogenization section; the extrusion processing temperature is divided into multiple temperature zones along the screw axis for control.
9. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, In the injection molding process, the mold adopts a multi-cavity hot runner system; the mold's cooling system adopts a conformal cooling water channel design.
10. The method for preparing a starch-based biodegradable lunch box according to claim 1, characterized in that, The aging process is carried out in a constant temperature and humidity chamber, and the aging temperature and relative humidity are controlled within a preset range; after aging, the moisture content is tested.